2017
DOI: 10.1109/taslp.2016.2634123
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal Crowdsourcing for Transcribing Handwritten Documents

Abstract: Abstract-Transcription of handwritten documents is an important research topic for multiple applications, such as document classification or information extraction. In the case of historical documents, their transcription allows to preserve cultural heritage because of the amount of historical data contained in those documents. The transcription process can employ state-ofthe-art handwritten text recognition systems in order to obtain an initial transcription. This transcription is usually not good enough for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Domain knowledge can be defined as the degree of subject familiarity with participants (Ju, ). Previous research indicated that participants with relevant domain knowledge usually provide high quality transcripts (Granell & Martinez‐Hinarejos, ). Thus, we believe that domain knowledge plays an important role in affecting the task completion of crowdsourced manuscript transcription.…”
Section: Related Work and Hypothesesmentioning
confidence: 99%
“…Domain knowledge can be defined as the degree of subject familiarity with participants (Ju, ). Previous research indicated that participants with relevant domain knowledge usually provide high quality transcripts (Granell & Martinez‐Hinarejos, ). Thus, we believe that domain knowledge plays an important role in affecting the task completion of crowdsourced manuscript transcription.…”
Section: Related Work and Hypothesesmentioning
confidence: 99%
“…This system was improved by adding a line selection module that allows us to optimize the collaboration effort (CE) . Then, it was tested in a real scenario where the speech collaborations were acquired from mobile devices …”
Section: Related Workmentioning
confidence: 99%
“…28 Then, it was tested in a real scenario where the speech collaborations were acquired from mobile devices. 7 In this work, the data fusion and lattice transformation performed by this crowdsourcing framework is studied. Moreover, we experimented with the integration of the crowdsourcing framework and the CATTI system.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations